2022
DOI: 10.3390/medicina58091174
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Sectional Study Examining the Association between Physical Activity and Perinatal Depression

Abstract: Background and Objectives: International organisations recommend that women without illness should have regular moderate-intensity physical exercise throughout their pregnancy and postpartum period as a measure to prevent possible pathologies in both the mother and the newborn. Physical activity during pregnancy reduces the likelihood of depression during pregnancy and after childbirth, benefiting both the pregnant woman and the foetus. However, most pregnant women are known to be inactive. The Pregnancy Physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Our findings align with prior studies on pregnancy-related depressive symptoms. [ 20 , 21 ] However, previous research on the relationship between pregnancy-related PAL and depressive symptoms is limited. Therefore, it may be necessary to expand the sample size for further exploration.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings align with prior studies on pregnancy-related depressive symptoms. [ 20 , 21 ] However, previous research on the relationship between pregnancy-related PAL and depressive symptoms is limited. Therefore, it may be necessary to expand the sample size for further exploration.…”
Section: Discussionmentioning
confidence: 99%
“…Depression is a very frequent mental disease which influences diverse aspects of the quality of human life [1,2]. Its main symptoms include loss of interest and appetite, anxiety and melancholy, frustration, helplessness, weakness and feelings of guilt or shame [3,4]. The World Health Organization (WHO) has reported that 25% of individuals worldwide could experience a mental disease at some time in their lives, highlighting that depression constitutes a major contributing cause to the global rise in women's disability-adjusted life years [1,2,5].…”
Section: Introductionmentioning
confidence: 99%